Study about Trioza erytreae: An Approach to Feeding and Oviposition Preference on Conventional Citrus Rootstocks - Francisco J. Arenas-Arenas; Juan M. Arjona-López; Aurea Hervalejo; Nancy Montero; Carlos Álvarez; Estrella Hernández-Suárez (New Visions in Biological Science Vol. 8, 2022)
The Mediterranean Basin is the second largest citrus-producing region in the world and Spain is the highest producer of this region. Huanglongbing (HLB) is the most important and devastating citrus disease worldwide, the causal agents of which are three bacteria species that belong to the genus Candidatus Liberibacter. The main transmission of these pathogens is by two psyllid vectors, Diaphorina citri and Trioza erytreae. T. erytreae is a specific pest of plants from the Rutaceae family, which includes cultivated citrus. This insect has recently been detected in Mediterranean Basin countries, specifically in Spain and Portugal. The potential risk of HLB emergence has increased concern in the Spanish and Portuguese citrus growing areas, which require the performance evaluation of T. erytreae on conventional citrus rootstocks as a method for reducing the insect population. The aim of this work was to study the survival, development, oviposition and feeding preference of T. erytreae in non-grafted conventional citrus rootstocks. This study evaluates the preference of T. erytreae in potted plants of different conventional citrus rootstocks. Thus, six different non-grafted citrus rootstocks were used for these experiments: (a) Carrizo citrange; (b) Citrus macrophylla; (c) ‘Cleopatra’ mandarin; (d) Forner-Alcaide No. 5; (e) Forner-Alcaide No. 517, and (f) Poncirus trifoliata (‘Flying Dragon’). The behavior and survival of this psyllid was evaluated through the feeding preference of T. erytreae adults for different rootstocks and oviposition and survival of T. erytreae adults on the different citrus material. T. erytreae showed a clear preference for hosting and feeding on C. macrophylla, while Carrizo citrange was the most suitable rootstock for insect reproduction and survival followed by C. macrophylla. Conversely, P. trifoliata was the least attractive rootstock to T. erytreae adults and led to significantly lower T. erytreae survival. Our results suggest that conventional citrus rootstocks, such as Carrizo citrange and C. macrophylla, could increase T. erytreae populations.